Nonverbal Communication of Supervisors in The Mentoring Thesis Process: Perceptions Of English Students - Meilan Nirmala Shinta; Besse Darmawati (LP2M IAIN Sultan Amai Gorontalo, 2021)
The study examines students' perceptions on the thesis mentoringprocess regarding their nonverbal communication patterns in the English studyprogram, FKIP of Halu Oleo University. The scope and focus are kinesics,proxemics, oculesics, chronemics, paralanguage, and physical appearance.Thisstudy apply a qualitative approach. The data obtained employing interview anddocumentation are then analyzed by Miles and Huberman's theory using reduction,reporting, and verification. The subjects of the study are eight graduated studentsand two students in the mentoring process. The study results shows that the sixtypes of nonverbal which are most likely to be experienced more often andinfluentially are ‘kinesics’, which is like the supervisor's attitude serving thestudents. Other nonverbal types continue to take on roles but are not as influentialas kinesics. This study reveals that the importance of communication is able toincrease student attention and motivation in constructing ideas gained from theirsupervisors when the communication process is going well and vice versa.